2014
DOI: 10.1145/2491912
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of UML analysis models on source-code comprehensibility and modifiability

Abstract: We carried out a family of experiments to investigate whether the use of UML models produced in the requirements analysis process helps in the comprehensibility and modifiability of source code. The family consists of a controlled experiment and 3 external replications carried out with students and professionals from Italy and Spain. 86 participants with different abilities and levels of experience with UML took part. The results of the experiments were integrated through the use of meta-analysis. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
1
37
0
4
Order By: Relevance
“…Based on the results of the ex-post questionnaire, the authors concluded that possible explanations of these results could be that (1) the diagrammatic notation has poor scalability and for complex scenarios it becomes hard to understand, and (2) fully structured notation needs specific preparation and additional materials in order to be understood. Scanniello et al (2014a) conducted four controlled experiments with students and professional to investigate the effect of UML analysis models on comprehensibility and modifiability of source-code. The participants were asked to complete tasks using both treatments (i.e.…”
Section: Empirical Comparisons Of Software Modelling Notationsmentioning
confidence: 99%
“…Based on the results of the ex-post questionnaire, the authors concluded that possible explanations of these results could be that (1) the diagrammatic notation has poor scalability and for complex scenarios it becomes hard to understand, and (2) fully structured notation needs specific preparation and additional materials in order to be understood. Scanniello et al (2014a) conducted four controlled experiments with students and professional to investigate the effect of UML analysis models on comprehensibility and modifiability of source-code. The participants were asked to complete tasks using both treatments (i.e.…”
Section: Empirical Comparisons Of Software Modelling Notationsmentioning
confidence: 99%
“…Also, in the last years we have witnesses an increasing number of papers that tackle the impact of using models vs. not using them on aspects such as productivity and maintainaibility of the applications (see e.g. [37,6,22]). …”
Section: Background and Definitionsmentioning
confidence: 99%
“…It is important to mention some other important papers relating to the influence of the use of UML diagrams during software maintenance which were not found as part of [19] because of their dates of publication or because of the objective of the SLR: -Scanniello et al [12] used a family of controlled experiments to discover that the use of analysis UML diagrams (those obtained in an early phase or the development process, such as the requirements elicitation or analysis phase) does not significantly improve the comprehension and modifiability of source code with regard to the use of source code alone. These results are valid in the context of undergraduate students and small size systems related to well-known domains.…”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, low LoD diagrams, like analysis models, do not appear to be helpful for source code maintenance [12]. On the other hand, high LoD diagrams are better understood than low LoD diagrams when performing software development [14].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation